Investigating the Impact of STEAM Learning on Higher Order Thinking and Science Achievement - Linda Juliharti; Abna Hidayati; Yullys Helsa; Asrizal Asrizal (Ta'dib, 2024)
Development of the industrial era 4.0 emphasizes the need for higher-order thinking skills (HOTS), especially in science and science learning in elementary schools. The low level of high-level thinking skills and science learning outcomes of elementary school students is a current problem. This research aims to determine the effect of implementing the STEAM (Science, Technology, Engineering, Arts, Mathematics) Learning Model on high-level thinking skills and learning outcomes in Natural and Social Sciences (IPAS) of class V students at SDN 18 Kampung Durian. This type of research is quantitative research. The research design used was Nonequivalent Control Group Design. The population in this study were all class V students at SDN 18 Kampung Durian, totaling 52 students consisting of 26 students in class VA (experiment) and 26 student class VB (control). The data were analize using a prerequisite test in the form of a normality test, then homogeneity, and hypothesis testing using the t-test. The research results show that the application of the STEAM Learning Model significantly improves students' high-level thinking skills and science learning outcomes compared to conventional learning. The average score of evaluation of higher-order thinking skills and science learning outcomes in the experimental group was significantly higher than in the control group. The t-test statistical test of critical thinking skills and students' science learning outcomes showed significant differences between the two groups (Sig.0.000>0.05). STEAM learning can be an effective alternative to enrich students' learning experiences, provide real-world science contexts, and stimulate the development of higher-order thinking skills.┬á